Efficacy of Fucoidan from Brown Algae of the Okhotsk Sea Fucus Evanescens in Vaccination Against Seasonal Influenza in the Elderly People - T. S. Zaporozhets; S. P. Kryzhanovsky; E. V. Persianova; T. A. Kuznetsova; A. L. Shutikova; N. M. Shevchenko; N. N. Besednova (Антибиотики и Химиотерапия, 2020)
The efficacy of fucoidan from brown algae of the Okhotsk sea Fucus evanescens in vaccination against seasonal influenza in people requiring priority protection due to the high risk of disease and the development of post-infective complications (elderly people) was studied. 40 participants aged 57 to 82 years participated in a number of ways, starting from the day of vaccination (vaccine «Sovigripp») in the dose 100 mg 2 times a day for 30 days. Through 5 weeks after vaccination, the immune response to strains A/H1N1 and a/H3N2 in the elderly control group did not meet the criteria of the European Committee on patented drugs, the concentration of antibodies in serum did not differ from the baseline. In the group of participants taking fucoidan, the level of seroconversion and seroprotection was higher than that in the control group, the mean geometric titer (SGT) of antibodies to all 3 strains significantly exceeded that before vaccination. SGT of antibodies to influenza b virus after vaccination in the experimental group significantly exceeded the parameters of the control group. In titer-stratified pre-vaccination antibodies (